Metal cation-exchanged montmorillonite clay as catalysts for hydroxyalkylation reaction - Jha, Ajay; Garade, Ajit C.; Shirai, M.; Rode, C. V. (Applied Clay Science, 2013)
Several solid acid catalysts were prepared by exchanging metal cations such as Zn2+, Fe3+ and Al3+ with montmorillonite clay. Among these, Al-montmorillonite showed the highest acidity determined by the pyridine-IR as well as NH3-TPD methods. A systematic comparison of the performance of these catalysts along with parent montmorillonite was carried out for the hydroxyalkylation of p-cresol with formaldehyde to give 2, 2'-methylenebis (4-methyl phenol) (DAM). It was found that the activity of these catalysts was in accordance with the increase in acidity of parent montmorillonite after the exchange of cations in the order of Zn2+, Fe3+ and Al3+. The selectivity pattern was also influenced by the exchanged cations. Since Al-montmorillonite showed the highest conversion of 51% with 98% selectivity to DAM, the effects of various reaction parameters, namely, mole ratio, catalyst concentration, temperature, reaction time on conversion and selectivity pattern were also studied using the same catalyst This catalyst also showed an excellent stability as evidenced by its eight times reuse. (C) 2012 Published by Elsevier B.V.
Keywords: Cations-exchanged clay; Montmorillonite; NH3-TPD; Pyridine-IR